Hungarian Monitoring, 20 November 1988 . [Magyar rádiófigyelő], 1988. november 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On the phantom Palestinian state and consequences of the decision - Gorbachev's December meeting with Reagan and Bush - Decision of the Estonian parliament, and opinions of Gorbachev and Moscow press on the decision Domestic Affairs: - Reports on Károly Grósz's Madrid and Paris talks - János Kádár recuperates after small operation on his hand, will not take part in Central Committee session starting on Tuesday - Hungarian Jewish Cultural Association formed - Alliance of Young Democrats (Fidesz) wants to put forward candidates in parliamentary elections Külpolitika: - A fantom palesztin államról és a döntés következményeiről - Gorbacsov decemberi találkozója Reagannel és Bush-sal - Az észt parlament döntése és hogyan vélekedik az ügyről Gorbacsov, illetve a moszkvai sajtó Belpolitika: - Beszámolók Grósz Károly madridi és párizsi tárgyalásairól - Kisebb műtétet hajtottak végre Kádár János kezén. Mivel Kádár pihenésre szorul, nem vesz részt a KB kedden kezdődő ülésén - Megalakult a Magyar Zsidó Kulturális Egyesület - A FIDESZ jelölteket akar állítani a parlamenti választásokon